Respuesta :

Answer:

250

Step-by-step explanation:

First, we need to find h°g, which is the same thing as [tex]h(g(x))[/tex]

This means that we will take the function [tex]h(x)[/tex] and will replace each instance of x with [tex]x^2+x-6[/tex] as that is the value of [tex]g(x)[/tex]

[tex]h(x)=5x\\\\h(g(x))=5g(x)\\\\h(g(x))=5(x^2+x-6)\\\\h(g(x))=5x^2+5x-30[/tex]

Now that we have our composed function, we can find the y-value when [tex]x=7[/tex]

[tex]h(g(7))=5(7^2)+5(7)-30\\\\h(g(7))=5(49)+35-30\\\\h(g(7))=245+5\\\\h(g(7))=250[/tex]

ACCESS MORE